Possibilidades de inovação aberta com a utilização de dados governamentais abertos no contexto brasileiro - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present study aims to identify possibilities for open innovation in initiatives that aim to promote and standardize the openness of public data, in an open format. In order to meet the objective: the possible benefits and possible barriers inherent to Open Data government initiatives in the Brazilian context were identified; and can be encouraged as coproduction practices to enable open innovation; it was verified what results were obtained from the coproduction practices; It is recommended actions that contribute to the accomplishment of coproduction and possibly innovation in processes arising from the opening of government data. This paper presents the following research question: How can Open Government Data initiatives, in the Brazilian context, contribute to the open innovation process of the public sector? As a theoretical contribution, the following themes were addressed: open government data, innovation, open innovation, coproduction and innovation in the Public Sector. Through a case study, for purpose of data collection, interviews were conducted with actors related to the topic and analysis of technological artifacts (softwares and / or applications). The results are welcome from the opening of the data, an improvement in the development of public policies and a possibility of development of innovative services. A promotion of Hackathons by the government was identified as a strategy to promote coproduction. With regard to incentives for the citizen to co-produce with the government, the results point to the predominance of intangible incentives, such as a satisfaction in contributing to the government. The main objectives for the government for coproduction were the possibility of taking advantage of the collective intelligence of society for the development of solutions to problems and innovations. In this sense, check the ability of the DGA to promote a coproduction between government and society, enabling an open innovation. However, barriers have been identified to be overcome in order for this process to develop.
Possibilities for open innovation with the use of open government data in the Brazilian context
Keywords: Dados governamentais abertos; Inovação aberta; Coprodução; Open government data; Open innovation; Coproduction; CNPQ::CIENCIAS SOCIAIS APLICADAS